Comment on "Nucleation of Mesospheric Cloud Particles: Sensitivities and Limits" by L. Megner. Issue 4 (5th April 2019) - Megner, L.
Abstract: In my article "Minimal impact on condensation nuclei properties on observable mesospheric ice properties" (Megner, 2011, https://doi.org/10.1016/j.jastp.2010.08.006 ) I show that the observable bulk quantities of Noctilucent clouds are much less sensitive to the concentration of condensation nuclei than what previously has been believed. These results were challenged by Wilms et al. (2016, https://doi.org/10.1002/2015JA021764 ), who studied the effect of nucleation rate on cloud properties and find a sensitivity. In this comment I argue that the differences between the studies are less than they first appear: Both studies show a very limited sensitivity to ice condensation nuclei, especially when there are more than roughly 100 condensation nuclei per cubic centimeter. Observations do indicate that under normal conditions, there are at least around 100 particles per cubic centimeter in the region of formation, and thus that we are in the insensitive regime. Plain Language Summary: Noctilucent clouds and polar mesospheric summer echoes are both manifestations of ice particles near the summer polar mesopause. These ice particles are believed to form mainly on preexisting ice condensation nuclei. The characteristics and especially the concentrations of such nuclei have been considered important factors in determining ice properties. But to what extent is this true? Results from Megner (2011, https://doi.org/10.1016/j.jastp.2010.08.006 ) suggest that the observable mesospheric ice properties are fairly independent of the condensation nuclei characteristics. These results have been questioned by Wilms et al. (2016), who do observe a sensitivity. I here compare the studies and show that both indicate a very limited sensitivity to ice condensation nuclei, especially as long as there are more than 100 condensation nuclei per cubic centimeter. Observations indicate that under normal mesospheric conditions, at least this many condensation nuclei are indeed present, and thus that the exact number of condensation nuclei generally has little impact on the ice properties. Key Points: Observable NLC ice properties are rather insensitive to the number of condensation nuclei (CN) once it is above 100 per cubic centimeter Observations set a lower limit for the nucleation rate, in that it must allow for creation of 100 CN per cubic centimeter Thus, the atmospheric conditions, such as temperature and winds, rather than microphysics, govern the observational properties of NLC